Design And Implementation Of Automatic Garbage Monitoring System Using Iot Platform - V V Satyanarayana Kona, Subramoniam M (International Journal of Advanced Science and Technology, 2020)
In the current era, the entire world is facing different types of hygienic problems due to the polluted environment. This pollution is happening in different ways like water pollution, air pollution, sound pollution, solid waste solution, etc. Whatever pollution maybe that will affect human lives directly, hence it is necessary to minimize such types of pollutions. Comparing with villages the cities are more polluted so the humans, who are living in the cities, are also facing many more health problems than the village peoples. The technology is increasing day by day but human thoughts are not improving while reducing this pollution due to their laziness or their lack of awareness about environmental pollution. The government is taking different types of techniques to reduce pollution but their actions are not executed successfully because they are not getting co-operation from the peoples while reducing pollution. The current review is analyzing the solid waste collection process which was proposed by the different authors.